DEVELOPMENT OF CRITERIA FOR THE SECURITY OF INFORMATION RESOURCES IN LEARNING MANAGEMENT SYSTEMS - YAREMKO, Svitlana; NOVYTSKYI, Ruslan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The The article examines the basic concepts of information security in the context of Learning Management Systems (LMS); the sources of threats to information resources of such systems, including anthropogenic, man-made and natural ones, are investigated; the peculiarities of developing security criteria to ensure reliable functioning of LMS are highlighted. An analytical review of the most common standards and methodologies used in the world to protect information in learning environments is carried out.This made it possible to identify the advantages and disadvantages of modern approaches to the development of criteria for the security of information resources in learning management systems and to offer a number of recommendations for improving the organization of their information security. Particular attention is paid to the issues of confidentiality of educational data, ensuring the integrity of educational materials and uninterrupted access to platforms.Based on the analysis of modern learning management systems, the authors proposed the following criteria for assessing their security: the presence of data encryption; user authentication in the system; security monitoring; frequency of parameter updates; reliability of data protection; complexity of implementing security measures, etc. This made it possible to assess the security of the most common LMSs today and provide recommendations on the use of security measures. According to the authors, the prospects for further development of this area may be associated with the implementation of innovative security systems based on both information technologies and intelligent systems, which in general will allow for constant monitoring, prediction and effective elimination of all possible threats to the security of information resources of learning management systems.
Keywords: information security; learning management systems; security criteria; source of threat; educational environment; security standards; methods of information protection